Condensed tannin from Caragana korshinskii extraction and protection effects on intestinal barrier function in mice - Niu, Xiaoyu; Qu, Wei; Chen, Zhiyu; Li, Hui; Liu, Peinan; Sun, Mei; Yang, Jing; Xing, Yuanyuan; Li, Dabiao (Frontiers in Veterinary Science, 2025)
Caragana korshinskii tannins (CKT) were extracted by response surface methodology and the protection effect of CKT on the jejunal mucosal barrier function of mice was investigated. Firstly, this work presents the extraction, purification and characterization of CKT. The results show that the extraction conditions were as follows: extraction temperature was 52°C, extraction time was 95 min, liquid-solid ratio was 20:1 and acetone volume fraction was 62%. The extraction yield of the CKT was 5.34%. The CKT has a typical polyphenol peak with a molecular weight of 8.662 kDa and is composed of epigallocatechin, catechin, epigallocatechin gallate, epicatechin, gallocatechin, epicatechin-3-o-gallate and catechin gallate with a molar ratio of 1:8.88:2.65:1.55:1.92:0.49:0.14. Additionally, the CKT showed strong antioxidants capacity in vitro. Secondly, the protection effect of CKT on the growth performance and mucosal barrier function of the mouse jejunum was examined. Totally, sixty KM mice were randomly divided into six treatment groups (n = 10) using a single-factor completely randomized experimental design. The treatment groups were intragastrically administered with 0, 25, 50, 100, 200, and 400 mg/kg BW of CKT aqueous solution once a day. The gavage volume was set at 0.2 mL per 10 g of body weight, administered daily for 21 days. The results showed that CKT significantly improved growth performance and physiological state of mouse intestine. CKT strengthened the intestinal physical barrier by upregulating the expression of Occludin and ZO-1 and decreasing the levels of serum diamine oxidase (DAO) and D-lactate (D-LA). Regarding biochemical barrier, CKT could upregulate the activity and gene expression of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and decreasing the content of malondialdehyde (MDA) in jejunum tissues. Generally, CKT may be used as a functional feed additive to regulate intestinal mucosal function, thereby enhancing the health of the intestine and host.